P634 Trajectories of oral budesonide use in Crohn's disease cohort of Tuscan patients. (27th May 2021) - Bertani, L; Ferraro, S; Bartolini, C; Convertino, I; Giometto, S; Cappello, E; Valdiserra, G; Tillati, S; Blandizzi, C; Lucenteforte, E; Gini, R; Tuccori, M; et al.
Abstract: Background: Crohn's disease (CD) is an immune-mediated inflammatory chronic disorder of the gastrointestinal tract. The therapeutic approach includes firstly oral budesonide (OB), followed by immunomodulatory drugs and biologics. The aim of the present study was to identify and characterize adherence trajectories of OB in CD patients and related patterns. Methods: In this retrospective cohort study, data was retrieved from administrative healthcare databases in Tuscany, an Italian region. Patients were included if they had a first record of a diagnosis of ICD-9 or disease exemption or a first record of dispensation of OB as CD patient, in the period from 6/1/2011 to 6/30/2016 (index date, ID). Patients < 18 years old at ID or with history of data before ID < 5 years or follow-up of data after ID < 3 years were excluded. Patients with autoimmune hepatitis, cancer and no dispensation of OB were excluded from CD cohort. We considered as covariates sex, age, and number of concomitant drugs during the month before ID. We estimated adherence to OB monthly through the Medication Possession Ratio and computed trajectory of adherence treatment with a procedure consists into 3 steps: 1) computation of 24 statistical measures; 2) factor analysis; 3) cluster analysis. We described the adherence in the clusters. Results: 3333 patients were included CD cohort, among them 1262 were excluded for no dispensation of OB. 2071 were patients included the computation of trajectory of OB use. Trajectories' curves showed three difference clusters of adherences to OB, which identify two main subgroups of OB users: 925, 603 and 543 were the patients in each cluster. Cluster 1 is represented by a curve of adherence that rapidly decreased to 20–30% of adherence within 5 months. Instead, cluster 2 and 3 described patterns of a short therapy timing, with discontinuation within about 4 months, likely referring to an acute treatment of CD, typical treatment approach used in mild to moderate CD. Statistically significance differences were evidenced between covariates across the clusters. Conclusion: Trajectories' curves showed three difference clusters of adherences, which identify two main subgroups of OB users. Further analyses need to characterize the identified clusters in order to evaluate possible inappropriate use of drug (cluster 1) and potential switch to other therapies (cluster 2 and 3). Finally, these results could clarify drug use in patients with CD and provide new insights in order to improve management of patients by clinicians.